2009
DOI: 10.1111/j.1099-1123.2008.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Internal Audit Report Disclosure on Investor Confidence and Investment Decisions

Abstract: Current governance disclosure requirements include reports from management, the audit committee, and the external auditor. However, despite internal audit's prominence as a critical governance mechanism, external stakeholders lack information about the function. This study evaluates the extent that a descriptive Internal Audit Report (IAR) affects investor confidence and investment decisions. The results indicate that participants provided with an IAR had more confidence in financial reporting reliability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 67 publications
(104 reference statements)
2
41
1
2
Order By: Relevance
“…External stakeholders such as investors generally lack information related to the IAF. Survey and experimental research report that disclosure of information related to the IAF would increase stakeholder confidence in governance quality and potentially affect investment decisions (Archambeault et al 2008;Holt and DeZoort 2009). I find that IAF quality is negatively associated with accounting-related management misconduct even after controlling for observable predictors of accountingrelated management misconduct (see Dechow et al 2011).…”
Section: Using Proprietary Internal Audit Survey Data From the Institmentioning
confidence: 88%
See 1 more Smart Citation
“…External stakeholders such as investors generally lack information related to the IAF. Survey and experimental research report that disclosure of information related to the IAF would increase stakeholder confidence in governance quality and potentially affect investment decisions (Archambeault et al 2008;Holt and DeZoort 2009). I find that IAF quality is negatively associated with accounting-related management misconduct even after controlling for observable predictors of accountingrelated management misconduct (see Dechow et al 2011).…”
Section: Using Proprietary Internal Audit Survey Data From the Institmentioning
confidence: 88%
“…Interviewees in Archambeault et al (2008) state that a report on internal audit would not only be useful to various stakeholders, but could also increase IAF accountability and incentives to perform effectively. Holt and DeZoort (2009) found that participants in their experiment were more confident in financial reporting reliability and perceived the oversight of financial reporting to be more effective when provided with an internal audit report. for empirical tests I convert the estimated F-score to a probability using the following formula: exp(F-score) / (1 + exp(F-score)).…”
Section: Predicting Accounting-related Management Misconductmentioning
confidence: 90%
“…Les relations entre l'audit interne et le comité d'audit L'audit interne est l'un des pivots de la gouvernance des organisations (Archambeault, DeZoort et Holt, 2008 ;Gramling et autres, 2004 ;Holt et DeZoort, 2009 ;Mat Zain et Subramaniam, 2007 ;Prawitt, Smith et Wood, 2009 ;Rezaee, 2005). Ce point de vue est partagé par les directeurs de la fonction d'audit interne qui se considèrent comme faisant partie intégrante de la gouvernance (Buranby et Hass, 2009, p. 822).…”
Section: Les Relations Entre L'audit Interne Et Le Comité D'audit Et unclassified
“…Previous studies on IA in the developed world show that it has been firmly entrenched as a contemporary corporate governance mechanism (Eulerich, Theis, Velte & Stiglbauer, 2013;Soh & Martinov-Bennie, 2011;Holt & De Zoort, 2009;Sarens & De Beelde, 2006;Carcello et al, 2005;Gramling, Maletta, Schneider & Church, 2004). However, this is not always the case in developing countries because corporate governance mechanisms, including IA, are mostly still in a process of developing (Li, Park & Bao, 2014;Al-Matari, Al-Swidi & Fadzil, 2014;Sarens & Abdolmohammadi, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%